2014
DOI: 10.1177/0022022114534915
|View full text |Cite
|
Sign up to set email alerts
|

Untreated Depression Predicts Higher Suicide Rates in U.S. Honor Cultures

Abstract: Osterman and Brown demonstrated that U.S. honor states had higher rates of suicide than non-honor states and related this phenomenon to the higher incidence of depression and a reduced readiness to seek antidepression treatment in honor states. The present study critiques their research and re-examines the origin of the association between honor culture and suicide using a more expansive multi-year data set and controlling for culturally relevant factors (i.e., climate, gun ownership, population density, colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 49 publications
0
30
1
Order By: Relevance
“…Also, research indicates that people with a suicidal past (85) and people from regions with a high suicide rate (86) have less positive attitudes and lower intentions to help-seeking behaviors. In similar vein, Crowder and Kemmelmeier (87) showed that in regions with high suicide rates people are less likely to seek out psychiatric services for depression. Against this background, in our fifth hypothesis we tested whether national suicide rates are associated with attitudes towards suicide and suicidal persons in the countries investigated.…”
Section: Discussionmentioning
confidence: 86%
“…Also, research indicates that people with a suicidal past (85) and people from regions with a high suicide rate (86) have less positive attitudes and lower intentions to help-seeking behaviors. In similar vein, Crowder and Kemmelmeier (87) showed that in regions with high suicide rates people are less likely to seek out psychiatric services for depression. Against this background, in our fifth hypothesis we tested whether national suicide rates are associated with attitudes towards suicide and suicidal persons in the countries investigated.…”
Section: Discussionmentioning
confidence: 86%
“…Indeed, in our own Study 1, perceived shame and guilt were highly correlated ( r = .60). Further, since a state’s honor-dignity status and state-level collectivism are positively correlated ( r = .34) but are differentially associated with suicide (Crowder & Kemmelmeier, 2014), state collectivism was included as a covariate. Statistical significance of parameter estimates was determined using robust standard errors ( RSE ).…”
Section: Studymentioning
confidence: 99%
“…Personal well-being is often contingent on meeting cultural expectations (e.g., Diener & Suh, 2000; Tov & Diener, 2007), and suicide can serve as an ultimate “way out” when people cannot meet important cultural mandates (cf. Crowder & Kemmelmeier, 2017; Tov & Diener, 2007). As such, differences in cultural expectations for behavior can give rise to differences in cultural constructions of suicide.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations